Evaluating Families’ Opinions of Routine Influenza Vaccination in Children Under 5 Years of Age in Spain - Sílvia Burgaya-Subirana; Anna Ruiz-Comellas; Queralt Miró Catalina; Mònica Balaguer (Vaccines)
Background/Objectives: Influenza vaccination is the main method for preventing influenza. The objectives of this study are to evaluate the opinions of families on influenza vaccination and to determine the acceptance of influenza vaccination as a routine vaccine in children under 5 years of age. Methods: The method used was a descriptive cross-sectional study based on an ad-hoc survey. Between October 2023 and January 2024, an online survey was conducted among families with children between 6 months and 14 years of age attending paediatric consultations at a health centre. Results: A total of 388 families were surveyed. Out of these, 22.68% reported having ever vaccinated their children against influenza. The main reason for having them vaccinated was having received the recommendation from the paediatrician (68.18%). While 53.61% agreed with routine influenza vaccination, 53.09% did not intend to vaccinate their children against influenza in the 2023/24 period. The reasons for not vaccinating in 2023/24 were unawareness of the disease (29.41%), fear of unwanted effects of vaccination (27.94%) and lack of information about vaccination (19.61%). The reasons for vaccination in 2023/24 were protection of the child (81.87%), recommendation by the paediatrician (43.41%) and protection of the general population and susceptible persons (20.33%). Conclusions: Routine influenza vaccination is accepted by half of the parents. A lack of risk perception of the disease, concern about vaccine safety and lack of information are the main reasons for not vaccinating. It is essential to follow the health professionals’ recommendation to vaccinate.